Developmental and neurobehavioral toxicity of benzotriazole ultraviolet stabilizer UV-360 on zebrafish larvae - Lihan Xu; Donglai Sheng; Rong He; Yanlong Meng; Lili Tian; Yuhao Luo; Yingjia Wang; Rusidanmu Aizemaiti; Zhou An; Yuying Wang (PLoS ONE, 2025)
The presence of UV-360, a commonly utilized benzotriazole ultraviolet stabilizer, has been frequently detected in diverse environments and organisms. However, existing knowledge regarding the potential impacts of UV-360 exposure on organisms remains limited. To evaluate the influence of UV-360 exposure on zebrafish during their initial developmental phases. The study began with an assessment of the developmental impact of UV-360 on larval stages. Subsequently, the investigation focused on examining its effects on locomotor behaviors. Additionally, analyses were conducted on neuronal development, the expression of genes associated with neurotoxicity, and electrophysiological recordings. Finally, the research extended to an exploration of transcriptome-level gene expression profiles. Exposure to UV-360 exhibited significant adverse effects on larvae, evidenced by a marked reduction in hatching rate, decreased heart rate, and impaired development of total body length. Furthermore, UV-360 exposure induced notable behavioral alterations, malformations in spinal motor neuron axons, and a substantial decrease in both the area and volume of these axons. Additionally, the expression of neurotoxicity-related genes and electrophysiological spike activity were significantly altered by UV-360 exposure. Lastly, exposure to UV-360 triggered significant modifications in the transcriptomic profile of zebrafish larvae, with a considerable proportion of differentially expressed genes associated with signal transduction processes and the neuroactive ligand-receptor interaction pathway. The results of this study revealed a dose-dependent developmental and neurobehavioral toxicity associated with UV-360 exposure in zebrafish larvae. The observed modifications in neuroactive ligand-receptors and disruptions in neurotransmitter systems suggested a potential mechanism for the neurotoxicity induced by UV-360 exposure in zebrafish larvae. These findings contribute significantly to the understanding of the toxicological effects of UV-360 on zebrafish larvae and provide strong evidence to help clarify the mechanisms of UV-360-induced toxicity.